Plotinus’ νοητή ουσία means substance paths to the Absolute - Robert Warchał (Warszawskie Studia Teologiczne)
The main issue of this paper is the role of νοῦς, or mind, as a condition for νοητής ουσίας. The activity of self-conscious self-knowledge within the framework of the noetic view of the Absolute is the ultimate and most important category for the author. Plotinus transcends the traditional dualism of being and non-being by showing that mind and soul are integral components of immaterial reality. In doing so, he makes it clear that human self-knowledge has an existential-subjective quality, based on the capacity for spiritual intuition. Discovering and developing this truth leads to transcendence, which is the criterion for transforming an entity burdened by externality into a supra-gignified entity, one that is free from the limitations of time and space. The sensual world, represented by the κόσμος αισθητός, can be an obstacle to learning about one's own nature and realizing the path toward liberation from the yoke of the animal self. Of course, being, understood in a spiritual context, has ontological priority here. However, an entity that is limited by external conditions - can bring itself all the way up to intellectual life through knowledge of itself. It manifests itself in the ability of spiritual intuition and thus salvific metamorphosis toward the timeless and supra-ontic Absolute.  For Plotinus, this spiritual process of development represents an important truth about man. On the noetic view of the One, the identity of the self implies knowledge of the self in God, which is the central mystery of transformation and return to the supernatural source.